Do gender and school type disparities influence the relationship between sleep quality and aggressive behavior? A moderation analysis - Shengsheng Lai (Humanities & Social Sciences Communications)
Abstract In China, the relationship between sleep quality and delinquencies such as aggressive behavior of Chinese high school seniors (CHSSs) has rarely been paid attention to. This research on the impact of sleep quality on aggressive behavior of CHSSs has filled the gaps in previous research on aggressive behavior of adolescents. Based on 2140 CHSSs samples collected from the southern cities in mainland China in 2024, the correlations between sleep quality and aggressive behavior were analyzed by using the multivariable regression models. According to the empirical results of this research, it can be known that sleep duration of most CHSSs in the total sample was less than 6 h, which was lower than the 2022 official statistics results that the average sleep of Chinese CHSSs was 6.5 h; CHSSs with poorer sleep quality may be more likely to involvement in aggressive behavior. Importantly, this study identified gender as a statistically significant moderator in the relationship between sleep quality and aggressive behavior including physical aggressive behavior, while the moderating effect of school types was not found to be statistically significant. These findings indicate that interventions and preventive measures should be tailored to different genders to effectively address the occurrence of aggressive and violent behavior among CHSSs with poor sleep quality. Also, the most CHSSs have reached the age for full assumption of civil and criminal responsibilities stipulated in the Chinese Civil and Criminal Law, and a considerable proportion of CHSSs may have poor sleep quality. Therefore, the high schools and relevant departments of government should formulate feasible and effective differentiated measures for different genders to improve sleep quality of CHSSs, for preventing and reducing the delinquent behavior including aggressive and violent behavior that may occur subsequently.